Sistema de evaluación del desempeño técnico-táctico en voleibol, una propuesta sencilla (Evaluation system of the technical-tactical performance in volleyball, a simple proposal) - Hernández-Wimmer, Cristian; Tamayo-Contreras, Valentín; Aedo-Muñoz, Esteban; Rojas-Reyes, Cristian (Retos, 2021)
El propósito de esta investigación fue construir un instrumento de evaluación del desempeño técnico-táctico de los jugadores de vóleibol, que posibilite la toma de decisión por parte del entrenador. Las variables de estudio fueron la evaluación del desempeño técnico de los jugadores de vóleibol y la evaluación del desempeño táctico de un equipo de vóleibol, a través del programa Microsoft Office Excel®, que permitió registrar y acceder en tiempo real a la información durante el desarrollo de un partido. La evaluación de desempeño técnico abarcó fundamentos técnicos, con su respectiva categorización de valores. La evaluación de desempeño táctico del equipo se compuso por la organización de la levantada, el porcentaje de eficiencia técnica del ataque en k1 y k2, y el análisis de distribución de levantada y eficiencia de ataque por rotación. El programa consiste en 6 libros de Excel® que trabajan de manera interrelacionada. Los primeros cinco corresponden a los sets jugados y el sexto, al resumen de toda la información ingresada. Las hojas se dividen en: Activas (Hoja final, hoja general, hoja diferencia, hoja atqefi, hoja análisis atqk2 y hoja resumen por jugador), Intermedias (Datos y ATAQRSM), y Pasivas (Tablas). El instrumento de evaluación desempeño técnico-táctico aporta y desarrolla en el ámbito de la evaluación objetiva de los rendimientos técnicos-tácticos. Este instrumento presenta características de bajo costo y fácil operación constituyen fortalezas que beneficiarán a todos aquellos entrenadores que lo utilicen.Abstract. The purpose of this study was to build an instrument for evaluating the technical-tactical performance of the volleyball players, which enables a decision making by the coach. The study variables were the evaluation of the technical performance of the volleyball players and the evaluation of the tactical performance of a volleyball team. A computer tool for evaluating the technical-tactical performance of volleyball players was developed. Through a computer program established in Microsoft Office Excel, which allowed registering and immediately accessing the necessary information during the development of a game. The variable of technical performance evaluation covers the following technical foundations, with their respective categorization of values. The tactical performance evaluation variable of the team was composed by the distribution of the raised, the technical efficiency percentage of the attack in k1 and k2, and the analysis of raised distribution and efficiency of attack by rotation. The program consists of 6 Excel books that work in an interrelated manner. The first five correspond to the sets played and the sixth corresponds to the summary of all the information entered. The match data were entered in the story sheet, to codify the technical-tactical situations of the game full. The sheets are divided into: Active (Final sheet, general sheet, difference sheet, atqefi sheet, atqk2 analysis sheet and summary sheet per player), Intermediate (Data and ATAQRSM), and Passive (Tables). The instrument of statistical evaluation of the technical-tactical performance of volleyball players serves as a contribution to the entire national volleyball environment, for its development in the field of objective evaluation of technical performances. This instrument its low cost and easy operation are strengths that will benefit all those coaches that use it.